(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the study was to check criterion validity of (WISC-IV) fourth edition German version evidenced by the third edition of it (WISC-III), by applying it to a sample of (550) normal children and adolescents from damascus city at the age of (6 to 16,11) years. The sample subjects were equally distributed according to gender (225 males, 225 females), and according to age/grade category with an average of (50) subjects for each category with a time period of one year from the first grade to the eleventh grade. The subjects were chosen using the available accidental method from (13) public schools for basic and secondary education. The findings showed that all of the criterion validity coefficients of (WISC-IV) with the subtests included in it and for the four-factor domains, evidenced by the subtests included in (WISC-III) at each age/grade category from (6 to 16,11) years were positive and significant. That is, they ranged between (0,6 to 0,994), which were higher than (0.3) according to Metshell’s approach in explaining correlations related to criterion validity. The findings were explained based on consistency between subtests components for each of the third and fourth editions of (WISC). In other words, (WISC-IV) is a German translation of the original American (WISC-IV), and the latter is an extension to (WISC-III), which includes about (56%) of the third edition items. Also, these results are partially consistent with some similar criterion validity coefficients, and exceed them in others that are mentioned in the original guide at almost the same age category.